Kratom: Botanical Insights and Cultivation Practices for a Conspicuous Medicinal Tree Species - Mengzi Zhang; Annabella Lyndon; Brian Pearson; Christopher McCurdy; Abhisheak Sharma; Jianjun Chen (EDIS, 2025)
Kratom (Mitragyna speciosa) is a member of the family Rubiaceae, a group of plants known for producing diverse bioactive metabolites. Arguably, the most popular member of the Rubiaceae family is coffee (Coffea arabica), which yields seeds (coffee beans) that contain bioactive metabolites, including the central nervous system stimulant caffeine. Unlike coffee, kratom is a facultatively deciduous tropical tree native to Southeast Asia. Other species closely related to kratom include M. hirsuta, M. diversifolia, and M. parvifolia. This publication offers educational insights into the horticultural aspects of kratom based on empirical scientific research for anyone interested in cultivating it.